Shadows of Kurdistan. A Photographic Research of a Cultural Identity - Yazar, Murat (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
We are all born somewhere in this world. The nature around us is the first element to shape us, with all of the unique characteristics of that particular place. Then we give names to these characteristics and meanings to these places – names that come from within ourselves and are part of our culture. This project is part of my life story, which I have tried to tell through photography. It was a way for me to discover my culture as I turned back to myself and my identity. I was searching for the stories behind the lives of the Kurdish people with images. At times, it was difficult to truly see and document people in my home region because the political situation and the civil war had closed them off. People became afraid to share their lives and ideas and their identity. And so it took time for me to be allowed to enter their lives. But when I did, it was truly rewarding to see and understand them. As the walls between us fell, I realized how close I was – and yet, still so far from my culture and to the people who enrich it.